Summer marine heatwaves in the tropical Indian Ocean associated with an unseasonable positive Indian Ocean Dipole event 2012 - Li, Zhiyuan; Wu, Gangfeng; Xu, Chang; Zhu, Xiao-Hua; Long, Yu (Frontiers in Marine Science, 2024)
Marine heatwaves (MHWs) are anomalously warm events that profoundly affect climate change and local ecosystem. During the summer of 2012 (June-September), intense MHWs occurred in the tropical Indian Ocean (TIO) concurrently with an unseasonable positive Indian Ocean Dipole (pIOD) event. The MHW metrics (duration, frequency, cumulative intensity and maximum intensity) were characterized by northwestward-slanted patterns from west Australia to the Somalia coast. The analysis confirmed that these MHWs were closely associated with the unseasonable pIOD 2012. The weakening of Western North Pacific Subtropical High and strengthening of Australian High in spring induced an interhemispheric pressure gradient that drove two anticyclonic circulation patterns over the eastern TIO. The first anticyclonic circulation featured cross-equatorial wind anomalies from south of Java to the South China Sea/Philippine Sea, which led to strong upwelling off Sumatra-Java during the subsequent summer. The second anticyclonic circulation excited downwelling Rossby waves that propagated from the southeastern TIO to the western TIO. Thus, downwelling in the western pole and upwelling in the eastern pole led to a strong pIOD event peaking in summer, namely, the unseasonable pIOD 2012. These downwelling Rossby waves deepened the thermocline by more than 60 m and caused anomalous surface warming, thereby contributing to the occurrences of MHWs. With the development and peak of the unseasonable pIOD 2012, anomalous atmospheric circulation transported moisture from the TIO to the subtropical Western North Pacific (WNP), favoring a strong cyclonic anomaly that profoundly affected the summer monsoon rainfall over the subtropical WNP. This study provides some perspectives on the role of pIOD events in summer climate over the Indo-Northwest Pacific region.